Studi Perbandingan Pembebanan Gempa Statik Ekuivalen dan Dinamik Time History pada Gedung Bertingkat di Yogyakarta - Faizah, Restu (Universitas Muhammadiyah Yogyakarta, 2015)
Time history dynamic analysis is the most accurate method in seismic load calculation, but it is quite complicated and time consuming. For practical need in the field, it used the equivalent static analysis that is the simplified dynamic analysis. The main difference between the static and dynamic concept is on the building characteristic that is calculated in analysis. Dynamic concept calculates the mass, stiffness and damping, while in static concept, only calculates the mass. It is stated in SNI 1726-2012 that equivalent static analysis can only be performed for horizontally and vertically regular structure. Irregular building design, asymmetrical floor plan, and high-rise building can use dynamic analysis. This research compared the result of equivalent static seismic load and time history dynamic analysis on the reinforced concrete frame structure of 5 levels, 10 levels, 15 levels, 20 levels, 25 levels, and 30 levels. Time history dynamic analysis is done with the assistance of Matlab program and used of accelerogram of 2006 Yogyakarta earthquake as the seismic input. The result of this study shows that the calculation result of the equivalent static seismic load is quite accurate on the 5 levels building, because it gives larger requirement in designing the structure, compared to the time history dynamic analysis of the seismic load. While on the calculation of equivalent static seismic load on the 10 or more levels structure is considered as not accurate, because it gives smaller requirements in designing the structure, compared to the time history dynamic analysis of the seismic load.